Australian Universities Under Neoliberal Management: The Deepening Crisis - Connell, Raewyn (International Higher Education, 2015)
Australian universities were transformed from small colonial outposts of European education to a relatively large public higher education sector by national development funding. Neoliberal management since the 1980s has transformed the universities into export-oriented corporations, is placing severe stress on the younger workforce, and is generating a crisis in the production of an intellectual culture.